Heart Rate Variability in Obstructive Sleep Apnea: A Prospective Study and Frequency Domain Analysis - Gula, Lorne J (Ann Noninvasive Electrocardiol, 2003)
Background: Cyclic variation of the heart rate is observed during apneic spells in obstructive sleep apnea (OSA). We hypothesized that autonomic changes would affect frequency‐domain measures of heart rate variability (HRV). Methods: We studied 20 patients (15 men, 5 women, mean age 47.2 ± 12.2 years) with suspected OSA undergoing overnight polysomnography, and five patients (4 men, 1 woman, mean age 49.2 ± 8.6 years) with recently diagnosed sleep apnea undergoing polysomnography while wearing continuous positive airway pressure (CPAP). Holter monitors were applied during sleep studies and data were analyzed in 5‐minute blocks over the course of the night. Using spectral analysis, low frequency (LF) and high frequency (HF) powers were calculated for each interval. Overall mean and standard deviation (SD) for LF power, HF power, and the LF:HF ratio were recorded for each patient. Comparisons were made between patients with severe OSA (apnea hypopnea index (AHI) > 30, n = 8), moderate OSA (AHI 1–30, n = 5), without OSA (AHI < 10, n = 7), and patients wearing CPAP (n = 5). Results: Assessment of overnight LF or HF power revealed no significant difference between the four groups. The LF:HF ratio, which represents sympathovagal balance, was higher among those with moderate disease compared to normals and those with severe OSA (both P = 0.037). The standard deviation of the LF:HF ratio was higher among those with moderate disease compared to normals (P = 0.0064) and those with severe OSA (P = 0.0006). OSA patients receiving CPAP behaved like patients with moderate OSA, with increased SD of the LF:HF ratio. Conclusions: The observed changes in the LF:HF ratio and its SD suggest an increased sympathetic tone and discordance in sympathovagal activity in moderate OSA, which is blunted in severe OSA. CPAP may restore autonomic defects, characteristic of severe OSA, to moderate levels.